Phytochemical Screeningin E. setifolia (A. Rich) Raynal, Ethnomedicinal Plant from Bhandara District Maharashtra - Bhaisare Manmohan S; Kunjalwar SG (International Journal of Life Sciences, 2016)
Phytochemical investigation of traditionally used Medicinal Plant is Thus Valuable on two levels, Firstly as a source of potential chemotherapeutic drug andsecondly as a measure of safety for the continued use of medicinal plant. The whole plant, Eleocharis setifolia,(A.Rich) Raynal which are used as traditional folk medicine for the treatment of dysentery, bowel disorder and inflammatory diseases. Eleocharis setifolia (A.Rich) Raynal contain, alkaloid, Steroids, Flavonoids, terpens, which includes sesquiterpene hydrocarbons. This paper explain the evidence based information regarding the pharmacological activity of this plant. It has many uses as pollution abetment and is medicinally used in traditional Ayurveda system.